Post Schooling Human Capital Investments and the Life Cycle Variance of Earnings - Thierry Magnac; Nicolas Pistolesi; Sébastien Roux (Institute for the Study of Labor (IZA), 2013)
We propose an original model of human capital investments after leaving school in which individuals differ in their initial human capital obtained at school, their rate of return, their costs of human capital investments and their terminal values of human capital at a fixed date in the future. We derive a tractable reduced form Mincerian model of log earnings profiles along the life cycle which is written as a linear factor model in which levels, growth and curvature of earnings profiles are individual-specific. Using panel data from a single cohort of French male wage earners observed over a long span of 30 years, a random effect model is estimated first by pseudo maximum likelihood methods. This step is followed by a simple second step fixed effect method by which individual-specific structural parameters are estimated. This allows us to test restrictions, compute counterfactual profiles and evaluate how earnings inequality over the life-cycle is affected by changes in structural parameters. Under some conditions, even small changes in life expectancy seem to imply large changes in earnings inequality.
Keywords: C33; D91; I24; J24; J31; 330; human capital investment; earnings dynamics; post-schooling earnings growth; dynamic panel data